Fonds and archives of non-governmental organizations: challenges for records management - Morte Nadal, Tamara; Esteban Navarro, Miguel Ángel (Revista General de Información y Documentación, 2019)
The aim of this article is to identify and analyze the problems and challenges posed by therecords management of non-governmental organizations attending to the four archival functions:recordkeeping, preservation, arrangement and access. The method followed consists in the analysis ofthe most relevant scientific production in the form of a qualitative systematic bibliographic review.The experience of preservation and promotion of the archives of charities and volunteer societies ofthe United Kingdom is presented as a reference model. The main conclusion is that the records and archives of non-governmental organizations do not receive enough attention from their producers,authorities and archival doctrine, despite their value for the administrative work, transparency,accountability and reputation of their creators and for history. The development of internationalguidelines is proposed, based on the manuals published by the International Council of Archives andthe archivists of British NGOs, which would serve as the basis for national guides and resources. Inthe case of Spain, it is suggested that the archival authorities of the Autonomous Communities shouldplan and fund campaigns for the recovery and preservation of records through collaborationagreements with the associations operating in their territories.
Keywords: Non-governmental organizations; Charities societies; Archives; Fonds; Records management; Recordkeeping; Preservation; Arrangement; Access; United Kingdom; Spain